Specialised psychiatric beds and 24-hour residential care in Australia 2018–2019 – Comparative analysis and commentary according to international benchmarking. (October 2022) - Looi, Jeffrey CL; Allison, Stephen; Bastiampillai, Tarun
Objective: A commentary on Australian specialised private and public psychiatric acute and non-acute inpatient care, and 24-hour-staffed community residential care with regard to international benchmarks. Method: Descriptive analysis of specialised psychiatric beds from the Australian Institute of Health and Welfare (AIHW) with the WHO Mental Health Atlas 2020, and an international Delphi consensus on optimal and minimal psychiatric beds per capita. Results: Australian private sector beds have shown a 3.8% annual growth rate from 2014–15 to 2018–19, in contrast to relatively static public sector bed numbers. Australia's national combined public and private psychiatric bed number (hospital acute and non-acute, and 24-hour-staffed community residential) of 48.8 per 100, 000 population is lower than the WHO European (100.6) and World Bank High Income (69.2) medians, due to fewer community residential and non-acute beds. Australia's 40.9 general and stand-alone psychiatric beds per 100, 000 are below the Delphi consensus optimal level of 60 beds per 100, 000, but above the bed shortage threshold (30 per 100, 000). Conclusions: Rising bed numbers in private hospitals have contributed to Australian psychiatric inpatient capacity, although the level remains below comparable international medians. Recent initiatives to increase psychiatric bed numbers may signal a policy shift in the public sector, complementary to private and community care.